Challenges and Opportunities of Crowdsourcing and Participatory Planning in Developing Infrastructure Systems of Smart Cities - Parul Srivastava; Ali Mostafavi (Infrastructures, 2018)
The concept of Smart City aims to provide its citizens with infrastructure systems that make cities safer and more livable. One of the methods for doing so is collecting data from the crowd itself—termed crowdsourcing—and incorporating their ideas to improve the existing facilities, as well as build new ones to cater to their arising needs. This paper aims to inspect the attributes that govern crowdsourcing, evaluating its feasibility in attaining solutions in the present scenario. A systemic review of the existing literature on crowdsourcing platforms was conducted and major findings have been summarized adequately. The areas of environment, disaster management, public safety, innovation, transportation and health have been explored in connection to the existing crowdsourcing platforms and selected examples have been mentioned. Next, the attributes that affect crowdsourcing have been discussed in detail under three broad categories: (1) human characteristics; (2) data characteristics and (3) system characteristics. In the end, some recommendations for improvement in the implementation of the crowdsourcing platforms have been proposed for their enhanced applicability and effectiveness.